An objective multi-criteria approach to optimization using MOORA method and interval grey numbers - Stanujkic, Dragisa; Magdalinovic, Nedeljko; Jovanovic, Rodoljub; Stojanovic, Sanja (Technological and Economic Development of Economy, 2012)
Many real-world problems are complex and/or related to the manifestation of some form of uncertainty and/or prediction. Therefore the use of extended MCDM methods is more appropriate than the use of the other classic decision making methods. These methods are improved by the use of a form of fuzzy or interval grey numbers. In the field of operational research, during the previous period, numerous MCDM methods were formed, but one newly proposed, the MOORA method, is very specific and yet has no extension. Therefore, in this paper we combine concept of interval grey numbers and MOORA method in order to propose extended MOORA method which will be more appropriate to solve many complex real-world problems.